Mengkultivasi Spiritualitas Holistik: Pendampingan Peningkaatan Kualitas Ibadah Shalat bagi Kepala Keluarga di TPQ Manula Sambirejo Jogoroto Jombang - M. Yusuf; Iswanto, Juni; Ali Fikri, M. (Journal of Smart Community Service, 2023)
This research aims to cultivate holistic spirituality through mentoring to enhance the quality of prayer among heads of households in TPQ Manula Sambirejo Jogoroto Jombang. The background of this study originates from the increasing demand of heads of households to improve the quality of their prayers. The research method employed is the Service Learning approach, involving participants who are heads of households in TPQ Manula Sambirejo Jogoroto Jombang. The objective of this research is to provide practical guidance for institutions or communities interested in implementing similar mentoring activities to enhance the quality of prayer among heads of households. The findings of this research indicate that effective mentoring can improve the quality of prayer among heads of households. Through mentoring, heads of households can deepen their understanding of proper prayer techniques, comprehend the meaning and purpose of prayer, and apply spiritual values in their daily lives. The participation of participants in the mentoring activities is highly active, and the exhibited spirit and enthusiasm by the heads of households are remarkable.